Participacija v strokovnih centrih z vidika otrokove/mladostnikove osebne in šolske/poklicne biografije - Marovič, Mateja (Revija za elementarno izobraževanje, 2024)
The paper deals with the field of participatory action among individuals placed in professional centres, which represents a special conceptual challenge in both the theory and practice of such engagement. We present the results of a quantitative study involving 231 children/adolescents from all regional professional centres in Slovenia that provide education for children/adolescents with emotional and behavioural difficulties and/or disorders. The results show that the participatory involvement of children/adolescents in such institutions – especially in support processes that have a significant impact on their personal and school/professional life histories – is not encouraging and that, to a greater extent than in traditional forms of residential treatment institutions, this option falls in the domain of individuals placed in housing groups.
Keywords: institutional care; osebna biografija; participacija otrok/mladostnikov; participation of children/adolescents; personal life history; professional centres; school/vocational record; strokovni centri; šolska/poklicna biografija; zavodska vzgoja